Effect of phosphate ester addition on transverse strength and hardness of heat cured acrylic denture base material - abed karkosh, Zahraa S.; Hussien, Basima M.A. (Journal of Baghdad College of Dentistry, 2018)
Background: acrylic resin denture base consider a common denture base material for its acceptable cost, aesthetic and easy processing but still has disadvantages including easy of fracture and low impact strength. Material and method: The experimental group was prepared by addition of 15% phosphoric acid 2-hydroxyethyl methacrylate ester (PA2HEME) with polymethyl methacrylate monomer; the experimental groups was compared with the control one. The specimens were prepared according to ADA specification No. 12 with dimension 65 mm x 10 mm x2.5 mm (length x width x thickness respectively). The prepared specimens were tested by three-point flexural strength utilizing Instron Universal Testing Machine (WDW, Layree Technology Co.), Shore D hardness tester used to measure hardness test. Statistical analysis used student T- test, mean and standard deviation. Results: The result of PA2HEME group showed high significant reduction comparing to the control group for both transverse strength and hardness test. Conclusion: Mixing 15% of PA2HEME with 85% methyl methacrylate (MMA) can reduce the mechanical properties of new modified polymethyl methacrylate (PMMA) acrylic resin.